Factors influencing participation in psychosocial programming among orthopaedic trauma patients with PTSD. Issue 12 (December 2022) - Furdock, Ryan J; Feldman, Blake; Sinkler, Margaret; Connelly, Madison; Hoffa, Matthew; Simpson, Megen; Hendrickson, Sarah B; Vallier, Heather A
Highlights: One third of patients with PTSD participated in trauma recovery services programming. Patients with severe PTSD, higher level of formal education, and commercial insurance were more likely to participate. Participation in TRS may be improved by minimizing the participant commute to the program location and by increasing awareness of patient groups at risk for less engagement. Abstract: Introduction: Post Traumatic Stress Disorder (PTSD) commonly occurs following acute trauma. Post-injury outcomes are negatively impacted by PTSD. Trauma Recovery Services (TRS) programming was developed at our institution in 2013 to provide psychosocial programming that increases patient satisfaction with care and ability to return to work and decreases PTSD symptoms. We sought to identify factors that influence patients' decision to participate in programming. Methods: Over a 3-year period at a single, urban level 1 trauma center, 172 patients over the age of 18 screened positive for PTSD on the validated PTSD checklist for DSM-5 (PCL-5) screening tool. Demographic, socioeconomic, injury, and medical comorbidity information was collected. Variables were initially compared in a univariate manner via Chi-squared, Fisher exact, t -test, or Mann-Whitney U, as appropriate. Variables that had a p-value <0.2 on univariate analysis were entered into a backward stepwise logistic regression model to identify independent predictors of participation in TRS programming. Results: Mean age was 37.8 years. 70.1% of patients were male. The most common mechanisms of injury were gunshot wound (33.7%), motor vehicle crash (19.0%), and burn. 33.5% of patients participated in TRS programming. Nine predictors had p <.2 on univariate analysis and were entered into the stepwise regression model. Four predictors remained in the final model. Patients with private insurance (RR=2.2, p =.038), high school diploma or greater (RR=1.53, p =.002; Table 1), and PCL-5 score greater than 50 were more likely to participate in TRS programming (RR=1.42, p =.046). Patients who live 20 or more minutes away by car from TRS were less likely to participate in programming (RR=0.47, p =.065). Discussion: Patients with more severe PTSD, higher levels of education, and private insurance were more likely to participate in TRS programming. Participation in TRS and similar psychosocial programs may be improved by minimizing the participant's potential commute to the program location.